2015
DOI: 10.1038/onc.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

The role of Tcfap2c in tumorigenesis and cancer growth in an activated Neu model of mammary carcinogenesis

Abstract: TFAP2C/AP-2γ influences development of the mammary gland and regulates patterns of gene expression in luminal and HER2-amplified breast cancer. The roles of TFAP2C in mammary gland tumorigenesis and in pathways critical to cancer progression remain poorly understood. To gain greater insight into oncogenic mechanisms regulated by TFAP2C, we examined mammary tumorigenesis in MMTV-Neu transgenic female mice with or without conditional knockout (KO) of Tcfap2c, the mouse homolog of TFAP2C. Loss of Tcfap2c increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
5
14
0
Order By: Relevance
“…However, we also identified rare DARs not bound by any reprogramming factors, such as the promoter region of Bex2 (Figures 6E, S6H, and S7C). Motif analysis for this peak suggested a Tfap2c binding site, which was confirmed by published ChIP-seq data (Park et al, 2015). We conclude that regions of hyperaccessibility, revealed only by dissecting the rare intermediates poised to reprogram, identify key cis-regulatory elements critical for reprogramming.…”
Section: Resultssupporting
confidence: 85%
“…However, we also identified rare DARs not bound by any reprogramming factors, such as the promoter region of Bex2 (Figures 6E, S6H, and S7C). Motif analysis for this peak suggested a Tfap2c binding site, which was confirmed by published ChIP-seq data (Park et al, 2015). We conclude that regions of hyperaccessibility, revealed only by dissecting the rare intermediates poised to reprogram, identify key cis-regulatory elements critical for reprogramming.…”
Section: Resultssupporting
confidence: 85%
“…However, recent studies had revealed dual role of c-Myc in reprogramming, and indicated c-Myc can negatively influences reprogramming by inducing cell apoptosis and creating an epigenetic barrier together with NCoR/SMRT corepressors 52 . In our present study, we found Tfap2c can attenuated the 'side effect' of c-Myc in reprogramming by inhibiting c-Myc-induced apoptosis, in agreement with previous results that Tfap2c decreased apoptosis in an activated Neu model of mammary carcinogenesis 53 . Although the precise mechanism is remained to further investigated, the fact that AP2 transcription factor family function as a negative regulator of c-Myc by impairing DNA binding of c-Myc at specific sites prompts us to speculate Tfap2c may inhibit c-Myc-dependent apoptosis in similar way 54 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous work has established that TFAP2C regulates EGFR expression in both human and mouse models of the HER2-amplified breast cancer subtype (14). To determine whether similar mechanisms of regulation occur in luminal breast cancer, three ERα-positive luminal A cell lines were examined.…”
Section: Resultsmentioning
confidence: 99%
“…For example, vandetanib also has TKI activity against EGFR (13). Interestingly, it has recently been shown that EGFR is regulated by TFAP2C in HER2 breast cancer and neu -activated mouse mammary cancer (14). These findings generate several interesting questions.…”
Section: Introductionmentioning
confidence: 99%